A numerical investigation of gasoline/diesel direct dual fuel stratification (DDFS) combustion at high loads. (15th March 2022) - Zhu, Yizi; Zhang, Yanzhi; He, Zhixia; Wang, Qian; Li, Weimin
Highlights: A numerical study of gasoline/diesel DDFS combustion at high loads is conducted. DDFS can control HRR while maintain comparable thermal efficiency at high loads. The near-TDC injection of fuel with low reactivity is the key parameter for DDFS. The effect of injection strategy on DDFS combustion at high loads is highlighted. Abstract: High-load extension is one of the biggest challenges for the low-temperature premixed combustion strategies such as partially premixed combustion (PPC) and reactivity-controlled compression ignition (RCCI). Alternatively, a different dual-fuel combustion strategy, direct dual fuel stratification (DDFS) mode, which combines the benefits of PPC and RCCI by injecting gasoline and diesel into cylinder directly, is investigated in the present study. A comprehensive numerical comparison of PPC, RCCI and DDFS was conducted, and the effects of fuel property of the near top dead center (TDC) injection as well as different injection parameters on the combustion and emission characteristics of DDFS at a typical high load were revealed. The results indicated that DDFS can effectively control the combustion rate while maintain the thermal efficiency comparable to PPC and RCCI at high loads. For DDFS combustion, the near-TDC injection is the key parameter to control the heat release rate. However, soot emissions remarkably increase owing to the diffusion-combustion nature of the near-TDC injection, and adopting lower reactivity fuel such as methanol is a good approach to further reduce the peak pressure rise rate (PPRR) and suppress soot emissions. In addition, the diesel fraction plays a dominant role in controlling combustion phasing while the gasoline fraction serves as a more important role in combustion duration, and the effects of the start of injection of gasoline and diesel on the DDFS performance become more obvious as the gasoline and diesel fractions increase. From the perspective of load extension, a lower diesel fraction should be employed to avoid excessive PPRR, however, the diesel fraction and the start of injection should be coupled properly to avoid misfire.